Pengaruh Waktu Pemberian Mikroorganisme Lokal ( Mol) dari Daun Kelor Terhadap Pertumbuhan dan Hasil Tanaman Sawi Hijau (Brassica Chinensis Var.Parachinensis L) - Simporianus Jama; Ni Putu Pandawani; I Gusti Ngurah Alit Wiswasta; Putu Eka Pasmidi Ariati; Ramdhoani (Program Studi Agroteknologi Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
Environmentally friendly agricultural land management with the use of MOL is able to maintain soil fertility, preserve the environment while at the same time maintaining and increasing soil productivity. Moringa leaf MOL can increase soil nutrients and as a plant growth regulator. This study aims to determine the effect of giving Moringa leaf MOL and the effect of differences in timing of Moringa leaf MOL administration on the growth and yield of mustard greens (Brassica chinensis var. parachinensis L). The study used a Randomized Block Design (RAK) experimental design with 6 treatments and 5 replications. The results of observations at the time of harvesting the fresh weight of harvest and dry weight of harvest also showed that, the treatment of giving MOL at 2 weeks before planting gave the highest real harvested fresh weight and dry weight compared to other treatments. The conclusion from the results of this study is that the difference in the time of giving Moringa leaf MOL to mustard greens gives a significantly different effect on the growth and yield of mustard greens and giving Moringa leaf MOL at 2 weeks before planting on mustard greens gives the yield of fresh weight of harvest and dry weight of harvest. significantly higher than the results at the time of administration of other MOL. So it turns out that the treatment of giving MOL at 2 weeks before planting is the right time for giving Moringa leaf MOL because it can provide the highest real harvested fresh weight and dry weight of harvest compared to other treatments, namely reaching a fresh harvest weight of 9.64 g/plant and a dry harvest weight. 2.20 g/plant.